Clinical Characteristics and Prognostic Factors of Patients with COVID-19 - Ali Fuat; Havva Kocayigit; Kezban Özmen Süner; Ahmed Bilal Genç; Fatih Güneysu; Mehmet Köroğlu; Hande Toptan; Emel Yılmaz; Ertuğrul Güçlü; Hamad Dheir; Selçuk Yaylacı; Aziz Öğütlü; et al. (Sakarya Tıp Dergisi, 2022)
Objective: We aimed to determine the main demographic features of COVID-19, reveal the clinical differences to patients in other countries, evaluate severe adverse effects in terms of number and types of comorbidities, and provide information about prognosis possibilities. Materials and Methods: Patients’ records, followed at Sakarya University Hospital between late March 2020 and late April 2020 with a diagnosis of COVID-19, were evaluated for this study. Demographic features were noted retrospectively with records, and data were recorded in the MS Excel program for analysis with SPSS. Statistical significance was set at p lt; 0.05. Results: The records of 1443 cases, 704 (48.8%) women and 739 (51.2%) men, a mean age of 44.98 ± 18.72, were examined retrospectively. Among them, 9.9% were medical staff, 1.8% had a history of travel abroad, and 1.1% were pregnant. Radiological findings of 59.4% of our polymerase chain reaction (PCR) positive patients were compatible with COVID. The mean length of hospital stay was 4.5 days. Frequent comorbidities were hypertension, diabetes (DM), and ischemic heart disease. Eighty (5.5%) patients treated in intensive care (ICU) died. Conclusion: Based on the data of 1443 patients, the mean length of hospitalization of COVID-19 patients was 4.5 days, or followed up in intensive care, having DM and a long period of hospitalization, which increased mortality risk. None of the outpatients died.